2009
DOI: 10.1080/03009740802385423
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of spondyloarthritis in 504 Chinese patients with HLA‐B27‐associated acute anterior uveitis

Abstract: The prevalence of SpA was high in the Chinese population with HLA-B27-associated uveitis. The association with SpA indicated an earlier age of uveitis onset and a greater likelihood of having a higher number of uveitis attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
1
33
1
2
Order By: Relevance
“…59-61 HLA-B27 anterior uveitis is more prevalent in males with 66.5-75% of patients being male. 63, 64 This is important because HLA-B27 anterior uveitis is one of the most common types of uveitis in Western countries, accounting for 50-80% of anterior uveitis patients. 60, 61, 63, 65-67 Recently, a genome-wide association study showed that a single allele of HLA-B27 conferred an odds ratio (OR) of 66.8 for developing acute anterior uveitis and homozygosity conferred an OR of 130.6 when compared to HLA-B27 negative controls.…”
Section: Male Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
“…59-61 HLA-B27 anterior uveitis is more prevalent in males with 66.5-75% of patients being male. 63, 64 This is important because HLA-B27 anterior uveitis is one of the most common types of uveitis in Western countries, accounting for 50-80% of anterior uveitis patients. 60, 61, 63, 65-67 Recently, a genome-wide association study showed that a single allele of HLA-B27 conferred an odds ratio (OR) of 66.8 for developing acute anterior uveitis and homozygosity conferred an OR of 130.6 when compared to HLA-B27 negative controls.…”
Section: Male Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
“…It is the most common form of anterior uveitis, accounting for 18–32% of all cases of anterior uveitis1. The typical phenotypes of HLA-B27-associated AAU are acute onset of unilateral alternating, non-granulomatous acute anterior uveitis, being characterized by significant cellular and protein extravasation into the aqueous humor including fibrin and hypopyon in the anterior chamber, high tendency for recurrences, and significant association with other HLA-B27-related diseases such as seronegative spondyloarthropathies (SpA)2. Considering the high frequency of recurrent attacks and sever ocular complication, AAU is regarded as a potentially sever threat to version.…”
mentioning
confidence: 99%
“…These 387 patients with SpA had an earlier onset of uveitis (p=0.01) and a greater number (six or more) of flares (p= 0.03) when compared with the 117 AAU patients without SpA [28]. Interestingly, Munoz-Fernandez et al evaluated presence of enthesis lesions in patients with idiopathic recurrent AAU and noted that a high percentage of patients with HLA-B27-positive recurrent AAU without features of SpA showed evidence of enthesis lesions similar to those observed in patients with SpA.…”
Section: Undiagnosed Spa Common Among Patients Presenting With Uveitismentioning
confidence: 93%
“…For example, in a study, 18 % of 394 anterior uveitis patients had SpA, and for 41 % of these SpA patients, uveitis was the first interaction with medical care for underlying SpA [27]. Now, if we look at the prevalence of underlying SpA in HLA-B 27-positive uveitis patients only, it has been reported to be very high, and two recent studies have shown this to be as high as 76 % [28,29].…”
Section: Undiagnosed Spa Common Among Patients Presenting With Uveitismentioning
confidence: 99%